Transforming Hajj Service Accessibility Policy: Towards Equitable Distribution of PLHUT Infrastructure in Remote Areas of Indonesia Based on Spatial Justice - Muhamad Dzulham (POKJANAS Bekerja Sama Biro Perencanaan dan Penganggaran, Sekretariat Jenderal Kementerian Agama RI, 2026)
This policy paper aims to analyze the problematic inequality in access to Hajj and Umrah services in Indonesia, triggered by the limited physical infrastructure of the Integrated Hajj and Umrah Service Centers (PLHUT) in remote areas. The main problem identified is the centralization of services trapped in a volume-based budget allocation paradigm and systemic dependence on the SBSN financing scheme, thus ignoring the needs of pilgrims in areas with extreme geographical difficulties. The methodology used in this policy study is a qualitative-descriptive approach with the William N. Dunn model of policy analysis. Evaluation is carried out through a scoring technique on five policy alternatives based on the criteria of effectiveness, efficiency, adequacy, equity, responsiveness, and accuracy. Data were collected through document studies of ministry performance reports, public service monitoring surveys, and related regulatory frameworks. The analysis results indicate that current policies tend to prioritize fiscal efficiency over spatial equity, which results in high logistics costs and the risk of fraud for pilgrims in remote areas. As a strategic solution, this study recommends regulatory transformation through the issuance of a Ministerial Regulation on Minimum Accessibility Standards in the 3T Regions, shifting the development paradigm toward a needs-based approach. The study's conclusion emphasizes that equitable distribution of PLHUT infrastructure through funding diversification and optimization of satellite service points is an absolute prerequisite for realizing inclusive and equitable Hajj services throughout Indonesia.